Pharmacological Evaluation and Antifertility Activity of Aloe barbadensis Linn on female wistar rats. - Sunil Kumar Shah; Deenanath Jhade; Rajendra Chouksey (International Journal of Phytomedicine, 2017)
Ethanolic and Aqueous extract of Leaf of Aloe barbadensiswas study, antifertility activity in proven fertile female Wistar Rats at the doses 500mg/kg b.wt./day for 30 days. Different parameters were studied in female wistar rats including effect of Reproductive outcome, Anti-implantation, Abortifacient study and Estrogenic and Anti-estrogenic activity, Phytochemical were observed.,Aloe vera Leaves shown positive test for Alkaloids, Steroid, Flavonoids, Terpene, Carbohydrates and Tannin. The extract of Aloe vera has anti-fertility effect the control rats showed good number of litters. Treatment of animal with different extracts, resulted a significant (P< 0.05, P< 0.01). antifertility activity (42.2% and 7.8%) was exhibited by AAV and WAV respectively. After 21 days of the extracts free period, the antifertility effect of the extracts was reversed. The extract treatments with AAV, an increase in the resorption index (%) by the extract is an indication of failure in the development of the embryo. The mean percentage of anti-implantation and percent resorption (abortifacient) were found to be highest for AAV-29.46%, WAV -12.17, and AAV-32.96%, WAV-7.78% respectively. The decrement in implantation caused by the extracts may be due to estrogenic or anti-estrogenic activity. However, along with standard AAVexhibiting more potent estrogenic and less potent anti-estrogenic when compared with standard.Clinical assessment of Female antifertility agents should include acceptability, safety and efficacy during and after the treatment. The present study was therefore carried out to evaluate the claimed antifertility effect of Aloe veraleaf using different aspects of reproductive physiology in female wistar rats.